2013
DOI: 10.3390/ijms14034476
|View full text |Cite
|
Sign up to set email alerts
|

From Identification to Characterization of the Multiple Sclerosis Susceptibility Gene CLEC16A

Abstract: Multiple sclerosis (MS) is an inflammatory, demyelinating disorder of the central nervous system that develops in genetically susceptible individuals, probably triggered by common environmental factors. Human leukocyte antigen (HLA) loci were early shown to confer the strongest genetic associations in MS. Now, more than 50 non-HLA MS susceptibility loci are identified, of which the majority are located in immune-regulatory genes. Single nucleotide polymorphisms (SNPs) in the C-type lectin-like domain family 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 105 publications
0
32
0
Order By: Relevance
“…[41] The CLEC16A locus is pleiotropic, which was first found to be associated Type I Diabetes [42], then association was established with several other immune-related diseases, including autoimmunity, allergy. [43] By studying gene expression in human blood samples and Clec16a conditional knockout mouse model, we further found the correlation between CLEC16A gene expression and genotype status, and demonstrated the potential role of Clec16a in B cell development. [41] …”
Section: Dense Genotyping Of the Autoimmune Risk Locimentioning
confidence: 93%
“…[41] The CLEC16A locus is pleiotropic, which was first found to be associated Type I Diabetes [42], then association was established with several other immune-related diseases, including autoimmunity, allergy. [43] By studying gene expression in human blood samples and Clec16a conditional knockout mouse model, we further found the correlation between CLEC16A gene expression and genotype status, and demonstrated the potential role of Clec16a in B cell development. [41] …”
Section: Dense Genotyping Of the Autoimmune Risk Locimentioning
confidence: 93%
“…Association studies have identified several SNPs in CLEC16A gene (previously called KIAA0350) associated with the risk of developing several inflammatory diseases [10,[16][17][18][19][20][21][22][23][24]. In the present paper, we studied four polymorphisms (146529 A > G, 155804 G > C, 47905 C > G and 64135 C > T) located in the CLEC16A gene.…”
Section: Discussionmentioning
confidence: 99%
“…CLEC16A presents four important SNPs, two in the intron 19 [position 146529 A > G (rs12708716) and position 155804 G > C (rs12917716)] and two in the introns 10 and 11, respectively [position 47905 C > G (rs6498142) and position 64135 C > T (rs9925481)]. These SNPs have been associated with risk to developing several inflammatory diseases as type 1 diabetes, multiple sclerosis, juvenile arthritis, rheumatoid arthritis, IgA deficiency [10,[16][17][18][19], Addison's disease, myocardial infarction, hypertension, metabolic syndrome [20][21][22], chronic kidney disease [23], and inflammatory bowel diseases [24].…”
Section: Introductionmentioning
confidence: 98%
“…rs2903692 is located at a distance of 58 910 bp from rs12708716, the lead SNP associated with type 1 diabetes mellitus, and both SNPs are in tight LD (R 2 =0.96). The mechanism of implication of CLEC16A in immune diseases is not clearly established, 30,31 and it is possible that other genes in the region are responsible for the association of this locus with immune diseases. It is interesting that Chromosome Conformation Capture studies have demonstrated physical proximity of the promoter of the nearby DEXI gene and intron 19 of CLEC16A.…”
Section: Carotid Geometrymentioning
confidence: 99%
“…rs2903692 is located in intron 22 of CLEC16A at position 16:11144926. The 3 intronic variants on the CLEC16A sequence were added to the exome array because they have been reported to be associated with several immunity-related diseases, 30 particularly type 1 diabetes mellitus and multiple sclerosis. rs2903692 is located at a distance of 58 910 bp from rs12708716, the lead SNP associated with type 1 diabetes mellitus, and both SNPs are in tight LD (R 2 =0.96).…”
Section: Carotid Geometrymentioning
confidence: 99%